Implementation of Ahoy Melayu Medan Gymnastics in the Introduction of Indonesian Culture in Sanggar Bimbingan Wira Damai Kuala Lumpur, Malaysia - Anjur Perkasa Alam Pohan; Muhammad Sufawi; Rania Maulida; Haifa Safira (International Journal of Islamic Educational Research, 2025)
This study aims to implement Senam Ahoy Melayu Medan as one of the methods in introducing Indonesian culture at Sanggar Bimbingan Wira Damai, Kuala Lumpur, Malaysia. Senam Ahoy, which is a combination of gymnastic movements and Malay cultural elements, is expected to be an effective means to introduce Indonesian cultural values ​​to Malaysian society, especially the younger generation. Qualitative methods were used to understand the experiences and perceptions of participants towards this activity, data were collected through the triangulation method. The results of the study showed that Senam Ahoy not only functions as a physical activity, but also as a medium to convey the values ​​of Malay culture, history, and identity. In addition, this activity succeeded in attracting the interest of children at Sanggar Bimbingan Wira Damai to better understand and appreciate Indonesian cultural heritage. This study is expected to be a reference for the development of similar cultural programs in the future. This study concludes that the implementation of Senam Ahoy Melayu Medan at Sanggar Bimbingan Wira Damai contributes significantly to the introduction and preservation of Indonesian culture abroad, as well as strengthening social relations between Indonesian and Malaysian society.